HUBUNGAN RUTINITAS BEROBAT JALAN DENGAN TINGKAT STRES PASIEN CUCI DARAH DI RSU SEMBIRING DELI TUA - Jon Piter Sinaga; Ferry Prawira Gurusinga; Robinson Paulinus Sihombing (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Patients who get dialysis will have various problems that arise due to the malfunction of the kidneys. It appears every time until the end of life. It will be a physical stressor that affects various dimensions of life including bio, psycho, socio, and spiritual. The occurrence of stress cause the presence of stressors that perceived and perceived by individuals and a threat that can cause anxiety. Almost all cases of chronic kidney failure require dialysis, but dialysis cannot completely replace kidney function. Patients who get dialysis therapy every two times a week and spend several hours will make them experience different tension, anxiety, stress and depression for each individual. The purpose of this research was to determine the relationship of outpatient routines with stress levels of dialysis patients at Sembiring Hospital Deli Tua in 2018. The research is an analytical research using a cross sectional design approach. The population of this research were patients who get dialysis therapy at Sembiring Hospital Deli Tua with a total sample of 50 patients using purposive sampling technique. The results showed that statistically bivariate analysis with Chi Square test that there was a significant relationship between dialysis frequency (p = 0.018), dialysis duration (p = 0.044), and duration of dialysis (p = 0.001) with the patient's stress level washing blood at Sembiring Hospital Deli Tua. It is recommended to medical staff who are on duty in the Installation of Hemodialysis to improve the way of communicating properly to dialysis patients, providing a sense of comfort, both to patients and families so that patients are not stressed while undergoing dialysis routines at Sembiring Hospital Deli Tua.